TINGKAT PENCEMARAN PERAIRAN DANAU BUATAN PEKANBARU DITINJAU DARI PARAMETER FISIKA, KIMIA DAN BIOLOGI - Mazidah, Rohul; Mulyadi, Aras; Nasution, Syafruddin (Jurnal Kajian Lingkungan, 2013)
This study wasconducted inFebruary - April2012 in Buatan Lake Waters Pekanbaru City.Theaimed of this study was to determine of the pollution level of Buatan Lake waters base onofphysical, chemicalandbiological parameters. The method used was surveymethod.Samples were takenat4 (four) stationsand5 (five) pointseach stationwith samplingintervaloftimeoncea month. The result of this study showed that physical and chemicalparametersweretemperature 28.7 to 30.8°C, depth 1.4 to 3m, the brightness 46.3 to 70.9cm, pH5.7 to 6,dissolved oxygen 1.11 to 1.55mg/l, BOD54 to 5mg/l, COD 26 to 32mg/l, TSS39 to 48mg/l,total organic matter in the sedimen 22 to 33%, and most of the stasions dominatedbymudsubstrat.Macrozoobenthosfoundas many as3(three) species (Tubifexsp, ChironomusspandHesperocorixasp). The average of macrozoobenthosabundance was791 ind/m2. Base onstatistical analysis (Anova)found that no significant differences abundance between stasionsFcalc.≤ Ftab.was 0.90<4.76), as well as between months. It could be conclude that BuatanLake waters had been heavily polluted, only a few high tolerance organism could be survive.